PENGARUH ADIKTIF SMARTPHONE TERHADAP MOTIVASI BELAJAR SISWA SEKOLAH DASAR: Studi Kasus pada Siswa Sekolah Dasar di SD Negeri 2 Setu Wetan - Karisma Amalia Hadiyanti, - (2020)
Addictive smartphones often have a negative influence on elementary school students, including their motivation to learn. This study aims to determine the profile of the addictive behavior of using smartphones as a medium for learning elementary school students, to find out the motivation to learn primary school students who often use smartphones and how much influence the use of smartphones on the motivation to learn primary school students in Public Elementary School 2 Setu Wetan, Cirebon Regency. The research method used is the case study method, with a mix methods approach and using exploratory sequential design. The results showed a positive influence on the use of smartphones on motivation to learn elementary school students. Addictive behavior profile of the use of smartphones of elementary school students as a medium of learning that is using it for online tutoring, learning through educational videos on YouTube, students also use their smartphones to search for subject matter that is not yet understood through the internet, as well as sharing subject matter or giving assignments by teachers through Whatts group chat App. Students who often use smartphones have high motivation to learn, because students use their smartphones as learning media too. The smartphone usage profile influences elementary school students' learning motivation by only 0.4%. This means that 99.6% of elementary school students' learning motivation is influenced by other factors not examined. So, the effect of using a smartphone on motivation to learn elementary school students falls into a very low category. By increasing the positive use of smartphones by students, such as using it as a learning medium, it can increase motivation to learn elementary school students in Public Elementary School 2 Setu Wetan.